The life of Wesley - Southey, Robert, 1774-1843, author.
1 online resource
Keywords: "The Life of Wesley was one of Southey's most influential and bestselling works. This two-volume edition will represent the full text of the 1820 edition. It will include a comprehensive critical apparatus and introduction that will make sense of the major issues posed by the text and how it contributes to studies of both Southey and Romanticism. It will also examine the book's reception history, incorporating material from reviews of the period and detailing the controversy it caused in the Methodist community"--